(untitled) (Economic and Political Thought, 2023)
The article analyses modifications in American trade policy towards the PRC in the area of controlling access to advanced semiconductor technologies over the last few years. Semiconductors are an extremely important technology that underlies almost all modern industrial activities, especially those related to national security. This is the basis for other advanced emerging technologies of the future. Tightening American control over access to semiconductor technologies is one of the peaceful actions that can effectively slow down China’s plans to become a global hegemon in the 21st century. This goal is achieved by the CHIPS and Science Act of 2022, which strengthens American production, supply chains and national security, and creates a fund that invests in research and development, science and technology, and the workforce of the future to regain leadership in semiconductor manufacturing.